Front Cover: Comparison of Nitrogen Activation on Trinuclear Niobium and Tungsten Sulfide Clusters Nb3Sn and W3Sn (n=0–3): A DFT Study (ChemPhysChem 14/2022). Issue 14 (19th July 2022) - Gurti, Joseph Israel; Ding, Xun‐Lei; Wang, Ya‐Ya; Chen, Yan; Li, Wei; Wang, Xin
Abstract : The Front Cover shows that the strong triple bond of a dinitrogen molecule is dissociated when meeting a three‐body active site. The three giraffes stand for the three metal atoms and three S labels indicate sulfide ligands, while the blue sky and green grass imply the positive environmental impact of using greener approaches for dinitrogen conversion achieved by improved catalytic reactions. More information can be found in the Research Article by Xun‐Lei Ding and co‐workers .